2017
DOI: 10.1038/s41598-017-00777-6
|View full text |Cite
|
Sign up to set email alerts
|

Amide hydrogens reveal a temperature-dependent structural transition that enhances site-II Ca2+-binding affinity in a C-domain mutant of cardiac troponin C

Abstract: The hypertrophic cardiomyopathy-associated mutant D145E, in cardiac troponin C (cTnC) C-domain, causes generalised instability at multiple sites in the isolated protein. As a result, structure and function of the mutant are more susceptible to higher temperatures. Above 25 °C there are large, progressive increases in N-domain Ca2+-binding affinity for D145E but only small changes for the wild-type protein. NMR-derived backbone amide temperature coefficients for many residues show a sharp transition above 30–40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…CMPs reconstituted with a mixture of 50% WT and 50% D132N variant (WT/D132N) displayed significantly reduced myofilament Ca 2+ sensitivity of force generation (pCa 50 = 5.32 ± 0.03), with a rightward shift of 0.11 pCa units compared with CMPs reconstituted with 100% WT cTnC (pCa 50 = 5.43 ± 0.02) ( Table 2 and Figures 5A,B). Consistent with previous reports that compared 100% D145E with 100% WT (Landstrom et al, 2008;Pinto et al, 2009;Veltri et al, 2017a), we found that reconstitution with a mixture of 50% WT and 50% D145E (WT/D145E) significantly increased myofilament Ca 2+ sensitivity of tension (pCa 50 = 5.58 ± 0.04), with a leftward shift of 0.15 pCa units (Table 2 and Figures 5A,B). Interestingly, we observed no significant difference in myofilament Ca 2+ sensitivity of tension upon reconstitution of CMPs with a mixture of 50% D132N and 50% D145E (D132N/D145E) ( Table 2 and Figures 5A,B).…”
Section: Muscle Mechanicssupporting
confidence: 92%
See 3 more Smart Citations
“…CMPs reconstituted with a mixture of 50% WT and 50% D132N variant (WT/D132N) displayed significantly reduced myofilament Ca 2+ sensitivity of force generation (pCa 50 = 5.32 ± 0.03), with a rightward shift of 0.11 pCa units compared with CMPs reconstituted with 100% WT cTnC (pCa 50 = 5.43 ± 0.02) ( Table 2 and Figures 5A,B). Consistent with previous reports that compared 100% D145E with 100% WT (Landstrom et al, 2008;Pinto et al, 2009;Veltri et al, 2017a), we found that reconstitution with a mixture of 50% WT and 50% D145E (WT/D145E) significantly increased myofilament Ca 2+ sensitivity of tension (pCa 50 = 5.58 ± 0.04), with a leftward shift of 0.15 pCa units (Table 2 and Figures 5A,B). Interestingly, we observed no significant difference in myofilament Ca 2+ sensitivity of tension upon reconstitution of CMPs with a mixture of 50% D132N and 50% D145E (D132N/D145E) ( Table 2 and Figures 5A,B).…”
Section: Muscle Mechanicssupporting
confidence: 92%
“…It was previously shown that cTnC-depleted CMPs reconstituted with cTnC-D145E increased Ca 2+ sensitivity of steady-state isometric force generation (Landstrom et al, 2008;Pinto et al, 2011a;Veltri et al, 2017a). However, to our knowledge, the effects of cTnC-D132N or mixtures of these cTnCs have not been previously reported.…”
Section: Muscle Mechanicsmentioning
confidence: 82%
See 2 more Smart Citations
“…This implies all sensitizers tested in this study work by shifting the dynamic equilibrium of cTnC towards the fully open conformation, which possesses higher Ca 2+ affinity than closed cTnC. 9, 20 Despite this common mechanism of action each sensitizer showed distinct behavior which will be discussed in depth below.…”
Section: Resultsmentioning
confidence: 90%